Solar Chimney and Power Tower Techniques for Power Production in Nasiriya City - Hannun, Rafid M.; Khalaf, Mohammed H.; Husain, Amel Hashim (Journal of Petroleum Research and Studies, 2018)
The solar chimney and power tower are two of modern promised energy which can develop by low losses, simplicity and high power. In this paper, the solar chimney and fossil fuel power tower parameters are studied by using theoretical equations in computational fluid dynamics CFD that substituted in some computer programs such as MATLAP and FLUENT codes with additional related expressions. Five different models are used in this paper (Chimney height is: 12, 15, 20, 25, and 35 meter), (Diameter of collector base is: 5, 8, 10, 15, and 20 meter). The effect of inlet collector height, collector absorbability, solar radiation, ambient temperature, solar collector thickness and solar collector tilt angle are studied to find the other parameters and properties such as velocity distribution, power and efficiency of system. The erecting of power turbine is predicted by findings the velocity distribution between the base and chimney assembly. The numerical analysis was presented by using GAMBIT and FLUENT 6.3 to predict that high velocity at the expansion of chimney near the center of base – chimney bond position because of low density of air as a result to solar radiation flux (and burned gases cover collector in case of using the chimney for combustion of gases in oil refineries).. This position is very suitable for promoting and building the power turbine. The maximum power accumulated from these techniques is more than (6.7×105 Watt) where the velocity is (17.5 m/s). The study concluded that it is easy work to erect these chimney and power tower techniques closed to drilling and oil facilities in remote areas. So, all factors were studied to coincide with previous papers in this field.